Serviceability assessment of a steel pile supported wharf structure: a case study - Yuksel, Isa; Avsar, Tolga (Springer Int Publ Ag, 2025)
The objective of this case study is to ascertain whether an existing pile-supported wharf structure can withstand the service and seismic loads to which it may be subjected. Data pertaining to the materials and soil were collected in situ, and a mathematical model of the wharf was subsequently constructed. Initially, a series of capacity checks was conducted under service loads. Subsequently, a deformation-based assessment was conducted in accordance with the TCHSEC-2020 principles. Plastic hinges were then defined at the nodal points of the pile cap-beam connections by means of the lumped plasticity approach. The target displacement was calculated taking into account the free soil behaviour. The system was then subjected to a static pushover analysis for both of earthquake levels DD-1 and DD-3. In accordance with the TCHSEC-2020 code, performance evaluations must satisfy two distinct performance targets, which have been determined for two different earthquake levels, designated DD-1 and DD-3. The results showed that the wharf met the performance targets defined separately for DD-3 and DD-1 earthquake levels. It is concluded that the steel pile wharf meets the requirements of TCHSEC-2020 under operational and seismic loads as it meets the requirements of TCHSEC-2020.
Keywords: Assessment; Earthquake; Pushover; Steel pile; Wharf